International Undergraduate Students in Chinese Higher Education: An Engagement Typology and Associated Factors - Tian, Mei; Lu, Genshu; Li, Lijie; Yin, Hongbiao (Frontiers in Psychology, 2021)
This research adopted a typological approach to explore international students' academic engagement in China. Using data generated by a survey study involving 801 international undergraduate students at 34 full-time Chinese universities, this research developed an international student engagement typology, and examined important individual and learning environment factors associated with the engagement types presented in the typology. The international student engagement typology helps to understand and enhance international undergraduate students' learning experiences in Chinese HEIs. Although located in China, this research holds implications for practitioners in broader contexts striving for the sustainable development of international student education.